MODEL BIMBINGAN KELOMPOK BERBASIS ISLAMI UNTUK MENINGKATKAN SIKAP TERHADAP PERAN GANDA WANITA - Nadhifatuz Zulfa; Anwar Sutoyo; Edy Purwanto (IAIN Pekalongan, 2013)
A positive attitude towards the dual role of women will build a tendency to run dual role of women in accordance with nature of woman. The result of the study at SMK Baitussalam Pekalongan shows that dual role of women material is given less so that so many girls who have negative attitude towards the dual role of women. The purpose of this study was to obtain the Islamic-based group counseling model that can improve the attitude towards the dual role of women in senior high school students. This study used Research and Development, with the result: Islamic-based group counseling model was proven effective in improving attitudes towards the dual role of women in senior high school students. It was visible from Wilcoxon statistical test that revealed a significant (probability <0.05). The development of Islamic-based group counseling model should be used as a model of service in helping students of SMK to improve their attitudes towards the dual role of women